Consumer acceptance of upcycled craft beer: a New Zealand case study - Goodman-Smith, Francesca; Bhatt, Siddharth; Grasso, Simona; Deutsch, Jonathan; Mirosa, Miranda (Frontiers in Nutrition, 2023)
Upcycled foods are created from surplus food, edible food waste and by-products. Food and beverage brands are launching upcycled foods and promoting their product to consumers. Little is known about how consumers respond to upcycled foods, nor how these products can be most effectively promoted. To better understand marketing strategies for upcycled foods, two studies were conducted, one online (n=300) and one in retail stores (n=65) in New Zealand to examine differences in consumer sentiment toward upcycled beer. In both studies, environmental benefits were identified as the most important benefits of upcycled foods and information provision on pack and online were important promotional strategies. Consumers reported greater awareness and acceptance of upcycled food in-store, yet raised concerns relating to taste and price. Only 31% of participants surveyed in-store associated 'no negatives' with upcycled foods compared with 47% of consumers surveyed online. These findings help differentiate a potential promotion strategy for upcycled foods.